Testing the on-court efficacy of the NBA's age eligibility rule - Rodenberg, R.; Kim, J. W. (Journal of Quantitative Analysis in Sports, 2012)
The NBA`s age eligibility rule is controversial. To examine the on-court efficacy of the NBA's age eligibility rule, we test the effect of age of entry on NBA career performance. Our data set comprises the 332 players selected in the first round of the NBA draft from 1989 to 2000. Using censored normal regression models, we found that players drafted at a relatively younger age have more successful NBA careers across three different metrics. To explore a beneficial effect of one year in college, group selection bias tests were conducted by comparing differences in career success between "one and done" players and players who entere the NBA straight out of high school. The results were consistent with our main analyses players who moved into the NBA directly from high school generally perform better than players with a single year of college experience. We find no systematic evidence in support of the on-court efficacy of the NBA's age eligibility rule.